A Comparative Study on the Effects of Ziziphus Spina-christi Alcoholic Extracts on Growth and Structural Integrity of Bacterial Pathogens: Ziziphus spina-christi as a native antibacterial plant - Hossein Motamedi,; Seyyed Mansour Seyyednejad,; Zahra Hasannejad,; Fariba Dehghani, (Iranian Journal of Pharmaceutical Sciences, 2014)
In different folk medicine Ziziphus spina-christi is used for different purposes such as pneumonia, dysentery, scorpion stings, cough, constipation, intestinal worms and fever. The aim of this study was evaluation and comparing the antibacterial activity of methanolic and ethanolic extracts of Ziziphus spina –christi as well as subsequent structural changes in affected bacteria. For this purpose, ethanolic and methanolic extracts were prepared by 80% alcoholic solution. Antibacterial activity of these extracts was assessed using standard disc diffusion method against pathogenic bacteria. Sterile filter paper discs (6mm) were saturated by four different concentrations of each extract. The prepared discs were placed on lawn cultures of test bacteria and incubated at 37 0C for 24 h. After incubation the inhibition zone diameter around each disc was measured in millimeter. The induced changes in shape of affected bacteria were discovered using scanning electron microscopy (SEM). As a result of this study maximum inhibition zone diameter in case of methanolic extract were 18 and 14 against Staphylococcus aureus, Bacillus cereu, and in case of ethanolic extract was 15 mm for S. aureus and Proteus mirabilis. The methanolic extract of this plant was more effective against S. aureus and B. cereus than the ethanolic extract even at high concentration. While the ethanolic extract was more active on Proteus mirabilis. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) indexes of both extracts were equal (MIC= MBC=8 mg/ml) for S. aureus. The SEM analysis revealed cell deformation and irregular shape in both S. aureus and B. cereus. These results suggest significant antibacterial activity of this plant especially against S. aureus, which its resistant strains are currently a great hazard in infection treatment. So, this plant should be considered as a potential source for finding new antibacterial agents.